MANAJEMEN SDM ORGANISASI SEKTOR PUBLIK: PROBLEMATIKA DAN ALTERNATIF SOLUSI - Eris Yustiono (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Public sector human resource management tends to have been neglected. In practice, human resource has been positioned as complimentary asset of an organization and has no sufficient bargaining power. This condition leads to a condition in which organizations neglect their employees’ administrative development such as promotion, pension and so forth. Furthermore, at some point it will create hindrances for career path development, performance improvement, andpersonnel development as a whole. Negligence in human resource management after all results in public sector’s deteriorating productivity and dwindling capability to serve the citizens. This condition is usually worsened by inept leaders who are incapable to manage the organization’s human resource.